Rule-Based Synthesis of Chains of Security Functions for Software-Defined Networks - Schnepf, Nicolas; Badonnel, Remi; Lahmadi, Abdelkader; Merz, Stephan (Electronic Communications of the EASST, 2019)
Software-defined networks (SDN) offer a high degree of programmability for handling and forwarding packets. In particular, they allow network administrators to combine different security functions, such as firewalls, intrusion detection systems, and external services, into security chains designed to prevent or mitigate attacks against end user applications. These chains can benefit from formal techniques for their automated construction and verification. We propose in this paper a rule-based system for automating the composition and configuration of such chains for Android applications. Given the network characterization of an application and the set of permissions it requires, our rules construct an abstract representation of a custom security chain. This representation is then translated into a concrete implementation of the chain in pyretic, a domain-specific language for programming SDN controllers. We prove that the chains produced by our rules satisfy a number of correctness properties such as the absence of black holes or loops, and shadowing freedom, and that they are coherent with the underlying security policy.